2015
DOI: 10.1007/s13277-015-3811-6
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin increasing multidrug resistance protein 1 via hypoxia-inducible factor-1α contributes to multicellular resistance in colorectal cancer

Abstract: When cancer cells have been cultured as three-dimensional (3D) cultures or in vivo, they decrease sensitivity to anticancer drugs. This is called multicellular resistance, and the mechanism is not fully understood. Here, we report that E-cadherin increasing multidrug resistance protein 1 (MDR1) via hypoxia-inducible factor-1α (HIF-1α) contributes to multicellular resistance in colorectal cancer. The MDR1 protein level was higher in 3D cultures than in monolayer cells. When dispersed cells from 3D cultures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 34 publications
2
35
0
1
Order By: Relevance
“…In a similar approach, Luebke-Wheeler, Nedredal, Yee, Amiot, and Nyberg (2009) used an E-cadherin blocking antibody to inhibit the E-cadherin function on hepatocyte spheroids, which led to an improved cellular death through a caspase-independent mechanism. Liang et al (2016) also demonstrated that the E-cadherin knockdown in HCT116 colorectal cancer cells leads to a decrease on the MDR1 expression in spheroids. The data indicate that E-cadherins can mediate the spheroids drug resistance because of their influence on MDR1 levels via HIF factor-1α (HIF-1α; Liang et al, 2016).…”
Section: Presence Of Cancer Stem Cells (Csc)mentioning
confidence: 85%
See 3 more Smart Citations
“…In a similar approach, Luebke-Wheeler, Nedredal, Yee, Amiot, and Nyberg (2009) used an E-cadherin blocking antibody to inhibit the E-cadherin function on hepatocyte spheroids, which led to an improved cellular death through a caspase-independent mechanism. Liang et al (2016) also demonstrated that the E-cadherin knockdown in HCT116 colorectal cancer cells leads to a decrease on the MDR1 expression in spheroids. The data indicate that E-cadherins can mediate the spheroids drug resistance because of their influence on MDR1 levels via HIF factor-1α (HIF-1α; Liang et al, 2016).…”
Section: Presence Of Cancer Stem Cells (Csc)mentioning
confidence: 85%
“…Liang et al (2016) also demonstrated that the E-cadherin knockdown in HCT116 colorectal cancer cells leads to a decrease on the MDR1 expression in spheroids. The data indicate that E-cadherins can mediate the spheroids drug resistance because of their influence on MDR1 levels via HIF factor-1α (HIF-1α; Liang et al, 2016).…”
Section: Presence Of Cancer Stem Cells (Csc)mentioning
confidence: 85%
See 2 more Smart Citations
“…Western blot was performed as previously described 14-15. Cells were lysed in RIPA buffer with protease inhibitors and phosphatase inhibitors for 30 minutes on ice.…”
Section: Methodsmentioning
confidence: 99%